THE CORRELATION BETWEEN TRANSFORMATIONAL PROCESSES AND EMPLOYMENT IN THE DIGITAL ECONOMY (INNOVATIVE ECONOMY, 2025)
Ashcheulova O.M., Los V.O., Lobunets T.V.  THE CORRELATION BETWEEN TRANSFORMATIONAL PROCESSES AND EMPLOYMENT IN THE DIGITAL ECONOMYPurpose. The aim of the study is to conduct a comprehensive analysis of transformation processes in the digital economy and their impact on employment. and to identify areas of regulation that can ensure the adaptation of the labour market to new conditions.Methodology of research. The study is based on a combination of systemic and structural-functional approaches, which allows consider the digital economy as an integrated set of interrelated processes. Comparative analysis is used to compare transformation trends in different countries (the US, EU, China, India) and to substantiate conclusions about the polarisation of employment. Analysis of statistical and analytical sources (in particular McKinsey, WEF, ILO and national statistics) is used to empirically measure changes in the structure of employment, productivity and earnings. The content analysis method of regulatory documents (Platform Work Directive, Digital Services Act, OECD materials) was used to identify gaps in the institutional regulation of platform employment. The generalisation and synthesis of the data obtained provided the basis for causal conclusions about the interrelationship between technological change, military shock and institutional barriers.Findings. It has been substantiated that automation and the introduction of AI are reorienting labour market demand towards highly skilled professions, while reducing employment in mid-level professions. It has been established that the gig economy and remote employment are forming a new architecture of labour relations, which increases labour flexibility but reduces the level of social protection and income stability. Regional and age disparities in digital literacy in Ukraine based on the results of a national survey, which limits the access of part of the population to highly productive segments the labour market. A conclusion has been made about the lack of adequate regulatory and legal regulation of platform employment, which increases the vulnerability of workers times of economic and military shocks. It has been shown that the combination of technological transformations with demographic and military factors exacerbates the polarisation and requires targeted retraining and social protection policies. Originality. The study interrelationships were identified between key transformational processes (automation, AI, gig economy) and the quality of employment of the population, taking into account crisis factors and the institutional environment at the national level. Unlike existing approaches, the obtained results integrate technological changes with military and demographic challenges, allowing for a deeper assessment of the risks of labour market polarisation and social disparities. This approach creates the basis for the formation of targeted policies for retraining and adapting the social protection system, aimed at mitigating the polarising effects of digitalisation in the context of national and global challenges.Practical value. The results can form the basis for the formation of public policy aimed at combining the development of digital skills with the creation of effective mechanisms social protection for workers in new forms of employment. The obtained conclusions should be used in the development of institutional reforms that will ensure a balance between innovative growth and social justice in the labour market. The practical aspect of the study also lies in the possibility of integrating the Ukrainian labour market into the European digital space, taking into account the challenges of the war and post-war period.Key words: automation; gig economy; employment, institutional regulation, labour market; artificial intelligence; digitalisation.
Keywords: automation; gig economy; employment; institutional regulation; labour market; artificial intelligence; digitalisation